2010
DOI: 10.2967/jnmt.109.074146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 18F-FDG PET/CT with Retrograde Filling of the Urinary Bladder in Patients with Suspected Pelvic Malignancies

Abstract: The purpose of this study was to assess the feasibility of selective pelvic PET/CT with retrograde bladder irrigation in evaluating pelvic pathologies. Methods: Thirty-eight patients (22 women and 16 men), with a mean age of 61 y (range, 41-81 y) and a neoplastic background (most of them of pelvic pathology), were assessed with PET/CT. The most prevalent findings were urothelial (14 cases), gynecologic (12 cases), and rectal (7 cases) cancers. All but 3 patients had undergone previous surgical procedures or ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The results of this prospective cohort is also similar to that presented by Vicente et al [ 12 ] who showed that in lesions with low FDG avidity (N = 42) the addition of 4D-PET/CT decreased specificity (100% to 72%) due to additional false positive findings. However, there was an increase in the overall accuracy (from 45% to 62%), due improved sensitivity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this prospective cohort is also similar to that presented by Vicente et al [ 12 ] who showed that in lesions with low FDG avidity (N = 42) the addition of 4D-PET/CT decreased specificity (100% to 72%) due to additional false positive findings. However, there was an increase in the overall accuracy (from 45% to 62%), due improved sensitivity.…”
Section: Discussionsupporting
confidence: 90%
“…This may be because the lung nodules at both time points are still affected by respiratory blurring. The dual time point method assumes an increase in SUV uptake is indicative of malignancy but one needs to consider that the measurement of SUV in moving lesions is less accurate [ 5 , 9 , 11 , 12 ] . An additional confounding factor for lesions subject to the respiratory motion in standard WB-PET/CT is inaccurate attenuation correction due to mis-registration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, apart from previous transurethral resections and postoperative reactive changes, especially renal excretion of 18 F-FDG and subsequent accumulation of the tracer in urine and in the bladder render detection and assessment of local bladder tumors difficult. Some modifications have been introduced in order to bypass these problems, such as flushing the bladder [ 20 , 21 ], application of diuretics or early scanning 2–4 min after tracer injection. Unfortunately, still false-positive findings can be observed [ 21 ].…”
Section: Pet and Pet/ctmentioning
confidence: 99%
“…Several strategies have been proposed to overcome this limitation. [5678910] The most promising strategy seems to be delayed pelvic FDG-PET/CT imaging after adequate hydration and voiding. A limited number of small studies have assessed the role of delayed PET/CT in the detection of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%